The Effect of Moringa Leaf Liquid Organic Fertilizer and Trichoderma on Growth and Yield of Lettuce (Lactuca sativa L.) - Narudi Narudi; Rasmita Adelina; Dini Puspita Yanty; Sutan Pulungan (International Journal of Natural Science Studies and Development (IJOSS), 2026)
Lettuce (Lactuca sativa L.) is a vegetable with numerous benefits and high economic value. The study was conducted in Neighborhood VI, Pasar Sibuhuan Village, Barumun District, Padang Lawas Regency, North Sumatra, in March 2025. The research method is an experimental study, using a factorial randomized block design. The first factor is liquid organic fertilizer of moringa leaves with 3 levels, namely P0 = Without giving liquid organic fertilizer of moringa leaves, P1 = liquid organic fertilizer of moringa leaves (120 ml/L), P2 = liquid organic fertilizer of moringa leaves (220 ml/L). The second factor is Trichoderma with 3 levels, namely T0 = Without Trichoderma, T1 = Trichoderma (20 gr/polybag), P2 = Trichoderma (30 gr/polybag). The parameters observed are plant height (cm), number of leaves (strands), leaf length (cm), leaf width (cm) and fresh weight (grams). The results of the study showed that the administration of liquid organic fertilizer from Moringa leaves significantly affected the initial vegetative growth (height, leaf length) and production of lettuce plants (P1 dose of 120 ml/L), while the Trichoderma treatment also significantly affected the growth and production of lettuce plants. The dose of 30 g/polybag (T2) had a positive effect, especially in increasing the number and width of leaves, as well as supporting the formation of plant biomass. The combination of moringa leaf POC and Trichoderma yielded the best results for lettuce growth and yield. The P1T2 treatment combination (120 ml/L and 30 g/polybag) was shown to produce the highest plant height and fresh weight.